Influência do ambiente hiperglicêmico no desenvolvimento do melanoma e do adenocarcinoma de mama murinos - Sellani, Tarciso Almeida [UNIFESP] (2017)
Epidemiological studies reveal a strong correlation between diabetes and increased risk for development of some neoplasias. Diabetes and cancer have in common several risk factors such as age, obesity, diet and physical inactivity, and biological mechanisms that possibly associate both diseases include hyperinsulinemia, hyperglycemia and inflammation. However, there are no experimental evidences corroborating this association. The objective of this study was to evaluate the effect of hyperglycemia on the development of 4T1 murine mammary adenocarcinoma and B16F10-Nex2 murine melanoma in vitro and in vivo. Tumor cells 4T1 and B16F10-Nex2 were inoculated in streptozotocin-induced hyperglycemic BALB/c and C57BL/6 mice, respectively. Primary 4T1 tumor development and metastatic lung nodules were increased in hyperglycemic animals, which also showed decreased survival, and mice treatment with metformin, a hypoglycemic drug, decreased tumor development. There were no significative differences in vitro in proliferation, migration, and in nitric oxide, cytokine and proangiogenic molecules production by 4T1 cells cultivated in high glucose concentrations. Normo or hyperglycemic immunodeficient animals inoculated with 4T1 cells showed no differences on primary or metastatic tumor development, indicating that adaptive immune system components are responsible for increased tumor growth. Hyperglycemic animals inoculated with 4T1 cells showed increased IL-10 concentration and T regulatory lymphocyte percentage in tumor microenvironment, as well as increased IL-10 and tumor-specific antibodies in serum. T-CD4+or T-CD8+lymphocytes depletion reduced tumor development in this model. Hyperglycemic C57Bl/6 mice inoculated subcutaneously with B16F10-Nex2 cells showed increased tumor growth, decreased survival, and metformin-treated animals showed decreased tumor development. B16F10-Nex2 cells cultivated in high glucose concentrations in vitro showed an increased IL-10 secretion, responsible for a proangiogenic effect in vitro. Hyperglycemic immunodeficient animals were inoculated with B16F10-Nex2 cells, and only TLR4-deficient mice showed tumor development similar to their normoglycemic pairs, suggesting that TLR4-expressing cells are responsible for the increased tumor growth. Nitric oxide-producing macrophage are augmented in primary tumors of hyperglycemic C57Bl/6 mice, the depletion of macrophages led to a decreased tumor development, and the transfer of macrophages from hyperglycemic C57BL/6 to hyperglycemic TLR4-deficient mice induced an increased tumor growth in the last animals. Hyperglycemic C57BL/6 mice treated with L-NAME, a nitric oxide synthase isoforms inhibitor, showed a decreased tumor development and increased survival, indicating a macrophage and nitric oxide participation in the increased tumor development of B16F10-Nex2 cells in hyperglycemic mice. Our results suggest that there is an association between hyperglycemia and tumor development, but the mechanism involved in this association depends on the tumor analyzed. In the 4T1 murine breast adenocarcinoma model, the increased tumor development in hyperglycemic mice occurs due to the participation of the adaptive immune response of the host, while in the murine melanoma model B16F10-Nex2 the increased growth of the tumor in hyperglycemic mice depends on the nitric oxide produced by tumor infiltrating macrophages, together with increased IL-10 production by B16F10-Nex2 cells.